2012
DOI: 10.7812/tpp/11-127
|View full text |Cite
|
Sign up to set email alerts
|

The Power of the National Surgical Quality Improvement Program—Achieving A Zero Pneumonia Rate in General Surgery Patients

Abstract: ment Program (NSQIP) provides riskadjusted outcome measures for participating hospitals to use for performance improvement. This article summarizes its history and reports the two projects on postoperative respiratory complications-intubation >48 and pneumonia. It also explains the benefit of a severalhospital collaborative and describes development of a "playbook."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 14 publications
2
92
0
Order By: Relevance
“…The database has been shown to be the most effective database for determining postoperative outcomes. 26,27 Our study confirmed that MIP is associated with short hospital stays, decreased morbidity, and no difference in operative time.…”
Section: Commentsupporting
confidence: 89%
“…The database has been shown to be the most effective database for determining postoperative outcomes. 26,27 Our study confirmed that MIP is associated with short hospital stays, decreased morbidity, and no difference in operative time.…”
Section: Commentsupporting
confidence: 89%
“…3 This commitment of a health system to deliver the safest medical care possible for its patients requires the ability to detect and record complications. 4, 5 Hence, a key challenge for improving patient safety is an accurate and widely implementable means of identifying the occurrence of complications.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although 2 recent large-scale studies did not demonstrate statistically significant improvements in the incidence of complications in NSQIP-enrolled hospitals when compared with controls, 9,10 it is clear that participation in the ACS NSQIP can contribute to improved patient safety and provide a platform for quality improvement. For instance, participating hospitals have shown reduced rates of pneumonia 17 and urinary tract infections. 18 Using rigorous data collection techniques, the ACS NSQIP is able to track complications over time and increases transparency of surgical performance.…”
Section: Discussionmentioning
confidence: 98%